PENERAPAN KECERDASAN BUATAN PADA GAME “AIR STRIKE STTA” BERBASIS CLIENT SERVER PADA ANDROID - Eko Teguh Prasetyo; Nurcahyani Dewi Retnowati (Institut Teknologi Dirgantara Adisutjipto, 2015)
Smartphones with Android operating system is one proof that the very quickly progress of technology. Functions and services on Android smartphones is no longer just for communication but also for entertainment such as games. Application are made in this research is a game that applies artificial intelligence with pathfinding techniques and can be played in single player and two players using the wireless local area network as data traffic lane with distribution techniques client server and can be played on smartphones with Android operating system. Software used to create this game is the Unity 3D engine. Unity 3D is a game creator software that is very powerful at this time. By using Unity 3D can make a game in a variety of devices, one of which is on a smartphones with Android operating system. With the application of this game can be a means the entertainment for anybody.